The Moderating Impact of Local Communities’ Attitudes on Tourism Attributes towards Destination Competitiveness of Cat Museum in Kuching - Lim, Jason; Lo, May Chiun; Mohamad, Abang Azlan; Wan Hashim, Bin Wan Ibrahim (Human Resource Management Academic Research Society, 2020)
Tourism attributes such as destination image, tourists’ satisfaction and tourists’ perceived values are nothing new in the research study on destination competitiveness. These are considered as factors that affect the competitiveness of a destination, however local communities’ attitudes (LCA) have yet to be tested whether it has an influence on the relationships on all these three attributes against competitiveness. Hence, Cat Museum in Kuching has been selected as a research site to be tested on, as this site carries its own unique selling proposition and believed to be able to satisfy tourists and given an utmost distinguished value in their travel. This study has introduced the local communities’ attitudes into the framework as moderator to test out whether local communities have an influence on these attributes that eventually affect destination competitiveness. For this study, 150 sets of questionnaires in total were collected. Both Statistical Package for Social Science (SPSS) version 23.0 and Smart PLS (version 3.2.7) were used for analyzing the data collected. The findings revealed that destination image, tourists’ satisfaction and tourists’ perceived values were significantly impacting on destination competitiveness and were proven as positively affecting the destination competitiveness. The implications of the study were further discussed.